Highly selective hydrogenation of dimethyl oxalate to methyl glycolate and ethylene glycol over an amino-assisted Ru-based catalyst. Issue 83 (27th September 2022) - Song, Lei; He, Yan; Zhou, Changan; Shu, Guoqiang; Ma, Kui; Yue, Hairong
Abstract : A Ru/NH2 -MCM-41 catalyst was prepared via a coordination-assisted strategy for highly chemoselective hydrogenation of dimethyl oxalate to methyl glycolate ( ca. 100%) and ethylene glycol (>90%) at low reaction temperature (343–433 K). Abstract : A Ru/NH2 -MCM-41 catalyst was prepared via a coordination-assisted strategy for chemoselective hydrogenation of dimethyl oxalate with a high selectivity of methyl glycolate ( ca. 100%) and ethylene glycol (>90%) at reaction temperatures of 343 K and 433 K, respectively. The amino groups help to anchor and form stable electron-rich Ru active sites, which accounts for the excellent CO bond activation and hydrogenation selectivity.